Enhancing Risk Assessment in Toll Road Operations: A Hybrid Rough Delphi-Rough DEMATEL Approach - G. Ardi Pratama; Y. Latief; Bambang Trigunarsyah; L. Sagita Riantini; Lukas Beladi Sihombing (Salehan Institute of Higher Education, 2023)
This study aims to identify significant risks and their relationship to the successful operation of the Trans-Sumatra toll road in Indonesia. The research utilizes the Delphi and DEMATEL methods, along with rough set analysis, to identify and evaluate 28 risks associated with toll road operations in Sumatra. The research identifies 13 dominant risks, including policy changes, government intervention, inflation, financial distress, fluctuation of interest rate, fluctuation of currency, high cost of maintenance, low volume of traffic, competitive routes, overloading vehicles, many infrastructure defects, and natural disasters. In this case, natural disasters, inflation, and vehicles with excessive loads are the most dominant cause factors because those risks have the highest cause value based on the cause-effect diagram. Furthermore, the prominence diagram reveals that income risk, policy changes, and financial distress have notable implications for operational activities. The study presents a MCDM risk assessment approach that incorporates rough set analysis, providing a comprehensive understanding of the critical risk relationship factors for toll road operations. By integrating rough set analysis, this research contributes to the field of toll road operations and risk assessment. The identified risks and their relationships serve as a foundation for developing effective strategies for toll road operational management.Â Doi: 10.28991/CEJ-2023-09-09-03 Full Text: PDF